11=6x-3+x

Simple and best practice solution for 11=6x-3+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11=6x-3+x equation:


Simplifying
11 = 6x + -3 + x

Reorder the terms:
11 = -3 + 6x + x

Combine like terms: 6x + x = 7x
11 = -3 + 7x

Solving
11 = -3 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
11 + -7x = -3 + 7x + -7x

Combine like terms: 7x + -7x = 0
11 + -7x = -3 + 0
11 + -7x = -3

Add '-11' to each side of the equation.
11 + -11 + -7x = -3 + -11

Combine like terms: 11 + -11 = 0
0 + -7x = -3 + -11
-7x = -3 + -11

Combine like terms: -3 + -11 = -14
-7x = -14

Divide each side by '-7'.
x = 2

Simplifying
x = 2

See similar equations:

| 7/6a=14 | | 85=2(-5b+2) | | 2x+11=5x-1 | | y-2x=2x-5 | | 3/12=4/x | | 6=-8x+2x | | 3r^2-20r-7= | | 9x+4=6x+7 | | 17x-3=13x-15 | | 5-2(x-1)=11 | | 5.7=-0.6 | | 5(x+2)+38=-3x | | 2p+5q+3p+q= | | w+2/3=2w+1/5 | | v^2-13v+40=0 | | .7(x+60)+.5x=78 | | 8y+2(-1/4-2y)=3/2 | | 2(2x-3)=2(3x-2)/4 | | -9y-1=-8y-4 | | 1/7-5/2y-1/6y | | x/2-x+6/7=6 | | 0.22-0.03(x+2)=-0.04(3-x) | | 17-13=x/-5 | | 25x-2=40+4 | | 2x(2x-4)=0 | | 4.72f-0.5=-61.6f-8 | | 2.1k=9.66 | | ((2x-7)/x)=((x-2)/5) | | 7-3/4c=65 | | -8x+9x-13x= | | 4-3x=8(1-x) | | -7-3=9x+5-8x |

Equations solver categories